2010
DOI: 10.1007/s00408-010-9234-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Dioxide on Pulmonary Vascular Tone at Various Pulmonary Arterial Pressure Levels Induced by Endothelin-1

Abstract: There have been contradictory reports suggesting that CO(2) may constrict, dilate, or have no effect on pulmonary vessels. Permissive hypercapnia has become a widely adopted ventilatory technique used to avoid ventilator-induced lung injury, particularly in patients with acute respiratory distress syndrome (ARDS). On the other hand, respiratory alkalosis produced by mechanically induced hyperventilation is the mainstay of treatment for newborn infants with persistent pulmonary hypertension. It is important to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
1
21
0
3
Order By: Relevance
“…Therefore, a more precise understanding of the contribution of enhanced endogenous NO production toward pulmonary vasorelaxation, augmented PKG signaling, and attenuated smooth muscle ROCK activity secondary to CO 2 will require further study. However, work by others has suggested that pulmonary vasodilatory effects of CO 2 may be independent of NO (11). Other likely upstream mechanisms by which CO 2 may have limited RhoA/ROCK activity, not explored in this study, include attenuated oxidative and nitrative stress in the lung (33,39,49) and downregulated expression of endothelium-derived GPCR ligands, such as endothelin-1 (33,74).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Therefore, a more precise understanding of the contribution of enhanced endogenous NO production toward pulmonary vasorelaxation, augmented PKG signaling, and attenuated smooth muscle ROCK activity secondary to CO 2 will require further study. However, work by others has suggested that pulmonary vasodilatory effects of CO 2 may be independent of NO (11). Other likely upstream mechanisms by which CO 2 may have limited RhoA/ROCK activity, not explored in this study, include attenuated oxidative and nitrative stress in the lung (33,39,49) and downregulated expression of endothelium-derived GPCR ligands, such as endothelin-1 (33,74).…”
Section: Discussionmentioning
confidence: 76%
“…A possible implication of these observations is that benefits of CO 2 on PHT were related to the dose of CO 2 itself, rather than the degree of acidosis induced, in keeping with several ex vivo studies (11,67). Alternatively, recent evidence suggests that arterial ROCK activity is highly pH-sensitive, being decreased at both low and high intracellular pH (6).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, carbon dioxide was found to produce a cerebral protective effect in case of hypoxic/ischemic damage [23]. Some studies have examined the positive effect of hypercapnia on the potassium channel [11], antioxidant system [27], and blood circulation in the lungs [5]. In addition, there are also data indicating that apoptosis inhibition is affected by permissive hypercapnia [30].…”
Section: Discussionmentioning
confidence: 99%
“…The main mechanisms of these hypoxia effects are probably the increase in mRNA expression in early gene families [6], the activation of the K + channel by proteinkinase C [17], the activation of succinatoxidase oxidation [7], and genome reprogramming by HIF-1 redox-sensitive protein [12]. However, toxic effects of hypercapnia should be kept in mind; it consists of an acid-base balance shift toward acidosis development, metabolism depression, intracellular homeostasis, and mineral metabolism disorder, as well as in respiratory center work depression [1,5,10,23]. The negative effects of carbon dioxide described above manifest themselves at PCO 2 above 100 mmHg (30).…”
Section: Discussionmentioning
confidence: 99%